The Water Scarcity and Its Impact on Environmental Displacement in Dhi-Qar Governorate - Manar Majid Hameed; Sarmad Sajid Badr; Saleem Ethab Muhammad (Zanco Journal of Humanity Sciences)
Dhi Qar Governorate has recently begun to suffer from the consequences of climate change, especially the water deficit, the effects of which have appeared clearly on the various aspects of life in maintaining the economic, social and even cultural levels, because water enters into the various details and details of human life on the surface of the Earth, and Iraq is one of Within the global system affected by climate change, especially water scarcity, the volume of water imported into Iraq decreased, recording (31.24 billion/m3) during the year 2021 after it was (49.67 billion/m3) in the year 2020, which led to forced migration. To move large numbers of the population from their areas to other new areas, especially from agricultural areas and marshland areas, and cities are one of the targeted areas for displacement, the Ministry of Immigration and Displacement in Iraq / Dhi Qar Branch recorded the displacement of (8,498 families) due to the crisis of desertification and drought, and this portends an environmental and humanitarian catastrophe for the people. Both the lack of a safe environment and sufficient sources of livelihood for the population results in a group of other problems associated with it, including the spread of diseases, epidemics, and tribal conflicts, as is happening now in the marshland areas, the conflict over environmental resources.